Design and Build Application of Student Academic Guidance in the Electrical Engineering Informatics Study Program Sam Ratulangi University - Arif Harsowiyono; Virginia Tulenan; Yaulie Deo Y Rindengan (Jurnal Teknik Elektro dan Komputer, 2021)
Abstract — To counterbalance with the advanced digital development, where the technology and computers are getting shopisticated, making all recordings stored in a system to ease the analysis process. Until now, the Informatic Studies Program of Sam Ratulangi University has not yet recorded academic guidance activity. Therefore, the study program make a guidance book to take a notes. From the book will be created an application with the same data on academic guidance book, where the data will be recorded and stored in a system online by using user login system and having three user that consist of Student, Lecture and Head of Study Program that have it's own different features. This feature is created in the Android Mobile operating system by using Android Studio. The development method used is the Agile Model Extreme Programming development method with data collection through literature studies. In conclusion, with this online recording feature, users can more easily record on the mentoring process and assist study programs in analyzing the recorded data.Abstrak — Untuk mengimbangi perkembangan digital yang semakin maju, dimana teknologi dan komputer semakin canggih, membuat seluruh pencatatan disimpan dalam sebuah sistem guna mempermudah proses analisis. Program Studi Informatika Universitas Sam Ratulangi hingga kini belum merekam aktivitas bimbingan akademik. Oleh karena itu, program studi telah membuat sebuah buku bimbingan untuk melakukan pencatatan. Dari buku tersebut akan dibuat sebuah aplikasi dengan data yang sama pada buku bimbingan akademik, dimana data nya akan dicatat dan disimpan dalam sebuah sistem secara online. Fitur ini dibuat dalam sistem operasi mobile Android dengan menggunakan Android Studio dengan menggunakan sistem user login dan memiliki tiga pengguna yaitu mahasiswa, dosen dan kepala program studi yang masing-masing memiliki fitur yang berbeda-beda. Metode pengembangan adalah metode pengembangan Agile model Extreme Programming dengan pengumpulan data melalui studi literature. Kesimpulannya, dengan fitur pencatatan online ini pengguna dapat dengan mudah melakukan pencatatan pada proses bimbingan serta membantu program studi dalam melakukan analisis dari data yang terekam